The use of LADP for query operation in trader service - Farkhana Muchtara; Mohd KuFaisal Mohd Sidek; Ismail Fauzi Bin Isnina; Kiran Sanjay Degan; Salmah Fattah; Muhammad Zafran Muhammad Zaly Shah; Nor Anita Fairos Ismail; Zuraini Ali Shah (Elsevier, 2025)
This research investigates the potential of the Lightweight Directory Access Protocol (LDAP) to optimize query operations in the Object Management Group (OMG) trading service, emphasizing the need for swift query responses in distributed systems. By leveraging LDAP’s inherent strengths in read-intensive environments, this study proposes a solution to enhance information retrieval and search efficiency. Through a comparative analysis involving a trading service configured with LDAP versus one using a conventional database backend, the results highlight superior performance in query response times when utilizing LDAP. The findings underscore the efficacy of LDAP as a backend storage mechanism, particularly in scenarios demanding rapid data access, and suggest its suitability for improving the operational efficiency of trading services in distributed computing contexts.